Beyond the purchasing power parity: exchange rates, prices and interest rates in ASEAN-5 countries - Noreha Halid; Hawati Janor; Fauzias Mat Nor (Penerbit Universiti Kebangsaan Malaysia, 2009)
This study examines the association among price, exchange rates and interest rates in ASEAN-5 economies. Several studies have suggested the importance of the linkages between goods and assets market in the determination of exchange rates and one way to account for such linkages is to incorporate interest rate and prices. By using cointegration test, we found evidence on the long run relationship among the variables indicating the importance of interest rate and price on exchange rate when structural break is considered. The findings thus show that the linkages between goods and assets market found in developed countries has general applicability to other small open economies specifically for Malaysia only when structural break caused by the financial crisis 1997 is considered. The diferent in results far the sub period indicate that not only it is important to consider multivariate approach but also the impact of financial crisis in the future research examining exchange rate in ASEAN-5 countries.